The economic valuation of the Singapore haze - Deepa Thangamani (2015)
Transboundary haze has been affecting Singapore for many years with year 2013 reaching an all-time high record in PSI level. In response to this issue, the Singapore government imposed fines on companies contributing to the haze, at a level that could be deemed insufficient given the increasing affluence of residents and their desire for better air quality. This study aims to evaluate the sufficiency of fines in the area of social well-being using the contingent valuation technique. Robust regressions have been generated apart from multiple linear regressions, with respect to age, income, education level, hours of outdoor exposure, insurance, existing haze-related illnesses in family and household size. Survey results revealed that the average amount respondents are willing to pay (WTP) at the maximum per day to avoid PSI100 is larger than the maximum fine an errant company is liable for each day, per resident. From the results of eight multiple linear regressions, higher income earners and respondents with larger household size have on average indicated significantly higher WTP and willingness-to-accept (WTA) values to avoid and live with the haze respectively. Results from robust regressions however revealed that only income and insurance have significant influences in the values indicated by respondents. The extent of insufficiency in financial penalties as provisioned in the 2014 Transboundary Haze Pollution Act highlighted in this study on social welfare losses alone will provide a benchmark for policy makers in reviewing the Act, while factors that were found to affect haze valuations in this study will assist adjustments on haze valuations based on demographic profiles and behaviors.